An in vitro long-term study of cryopreserved umbilical cord blood-derived platelet-rich plasma containing growth factors—PDGF-BB, TGF-β, and VEGF. Issue 4 (April 2019) - Baba, Kyoko; Yamazaki, Yasuharu; Sone, Yumiko; Sugimoto, Yoshika; Moriyama, Kazuno; Sugimoto, Takayuki; Kumazawa, Kennichi; Shimakura, Yasuhito; Takeda, Akira
Abstract: Purpose: Umbilical cord blood-derived platelet-rich plasma (UCB-PRP) containing growth factors has attracted attention as a biomaterial useful for regenerative medicine. The osteoblastic differentiation of umbilical cord-derived mesenchymal stromal cells (UC-MSCs) can be induced by UCB-PRP. Materials and methods: Nine samples of UC and UCB were used to conduct an in vitro study that determined the contents of three growth factors (i.e., platelet-derived growth factor, transforming growth factor β-1, and vascular endothelial growth factor) and that examined, by staining with Alizarin red, their ability to induce the osteoblastic differentiation of UC-MSCs at the baseline, 3 months, and 3 years of cryopreservation. Results: The contents of growth factors in cryopreserved UCB-PRP were markedly elevated compared to those found in UCB at baseline. The samples of UCB that were added with cryopreserved UCB-PRP and those with bone morphogenetic protein-2 were stained granularly with Alizarin red, thus indicating the presence of calcium. The samples of UCB that were not added with UCB-PRP were not stained with Alizarin red. The above-mentioned contents and ability were maintained at 3 years of cryopreservation. Cryopreserved UCB-PRP possibly and advantageously induced the osteoblastic differentiation of UC-MSCs. Conclusion: The potential clinical application of cryopreserved UCB-PRP to regenerative medicine was suggested.